سوال کی شرعی ضرورت و اطلاق اور قرآنی اصطلاح یَسْئَلُوْنَکَ : عصری معنویت - Abdul Samad; Abdullah (الآفاق اسلامی و تحقیقی مجلہ)
In Islam, the pursuit of knowledge holds a fundamental position. This is why the very first revelation of Islam also draws attention to it. Asking questions in the pursuit of knowledge is also given primary importance, as Allah Almighty Himself teaches this method in the Holy Qur’an. Following this Qur’anic guidance, the noble Companions would promptly ask the Prophet Muhammad whenever they encountered any difficulty or ambiguity regarding a matter. These questions have been presented in the Qur’an under a specific expression: "Yas’alūnaka" (They ask you). Under this title, the Companions posed several questions, and their answers were conveyed through the Prophet. In the Qur’an, there are twelve questions mentioned with the phrase "Yas’alūnaka" across different verses, and the expression "Yas’alūnaka" itself is used fourteen times, indicating that two questions were repeated. Under the selected title of this research paper, a juristic and methodological (uṣūlī) study of these questions has been conducted in the light of selected Urdu Qur’anic commentaries, in order to explore how jurists and scholars of Islamic legal theory have derived various rulings and principles based on their respective frameworks, methodologies, and interpretative approaches.